Read alouds 2.0 in an Indonesian tertiary EFL classroom - Novianti, Nita; Abdurahman, Nur Hafiz (Indonesian Journal of Applied Linguistics, 2019)
Read alouds have long been advocated as a reading practice that is not only appropriate for children but also for adult learners. Empirical evidence shows that reading aloud could be an effective strategy for EFL students’ reading comprehension. However, its practice in EFL literature classrooms has received scarce attention. To fill this practical gap, this article reports on the adoption of read alouds 2.0 in a tertiary EFL literature classroom. The read aloud 2.0 aims to help students make meaning of literary texts. In this practice, blended discussion was carried out through Edmodo as a learning platform for virtual engagement between teacher and students and between students and their peers. The implication of this practice is that both teachers and students maximize their engagement with literary texts both face-to-face and virtually.